Toward a Definition of the Matter in Philosophy (Global Journal of Human-Social Science, 2023)
The definition of the matter which is still in use today is based on the method of formation of general notions proposed in his time by John Locke In doing so the matter is regarded not as something sensually existing but as a distraction from the distinctions of forms of matter already known to us This gave George Berkeley grounds for arguing that such an abstraction could simply be discarded without anyone even noticing it In his work Materialism and Empirio- Criticism objecting to G Berkeley Lenin corrected the definition of the matter by emphasizing that it is not just a philosophical category to denote objective reality but that the matter is copied photographed displayed by our senses existing independently of them In this way however V I Lenin only confirmed G Berkeley s view that to exist is to be perceived which he himself had previously challenged In the opinion of the author of the article V I Lenin s definition of the matter did not fully take into account the lessons of Hegelian dialectics which proves that the most general concepts are those that appear first It turns out that at this point the matter should be understood not as some abstraction from forms already known to us but as some of its pre-physical form whatever it may be But the pre-physical the form of the matter is not given to us in the senses Yet its objective existence is undeniable After all if we reject the prephysical form of the matter as G Berkeley ironically suggested we will destroy with it the physical basis of the world including ourselves However such an understanding of the matter raises the question of the beginning of its development in a new way
Keywords: metaphysics; matter; ideal; being; nothingness